Penggunaan Media Realia Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pecahan Di Kelas IIIA SDN Kertajaya IV/210 Surabaya - Mujiati, Titik (Jurnal Simki Pedagogia, 2022)
This study aims to improve the mathematics learning outcomes of fractions in class IIIA SDN Kertajaya IV/210 Surabaya by using realia media. This research was conducted at SDN Kertajaya IV/210 Surabaya in the second semester of the 2020/2021 academic year for two months. The research subjects were 29 students of class IIIA SDN Kertajaya IV/210 Surabaya. The data collection method uses tests and observations. The conclusion of the results of this study is that using realia media can improve learning outcomes in mathematics subjects with fractions for class IIIA students at SDN Kertajaya IV/210 Surabaya. This can be proven from the results of observations which show that in the first cycle the percentage of student learning completeness is 72%, then it increases in the second cycle to 100%. The average score of students in the first cycle was 77.76 and increased to 88.79 in the second cycle.